2011
DOI: 10.7150/ijms.8.623
|View full text |Cite
|
Sign up to set email alerts
|

Vapocoolant Spray vs Lidocaine/Prilocaine Cream for Reducing the Pain of Venipuncture in Hemodialysis Patients: A Randomized, Placebo-Controlled, Crossover Study

Abstract: Objective: Patients undergoing hemodialysis are repeatedly exposed to stress and pain from approximately 300 punctures per year to their arteriovenous fistula. This study was designed to measure pain associated with venepuncture during AVF cannulation and to compare the effectiveness of ethyl chloride vapocoolant spray, topical eutectic mixture of local anesthetics (EMLA) cream and placebo in controlling pain caused by venepuncture of arteriovenous fistula patients undergoing chronic hemodialysis.Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
110
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 19 publications
7
110
2
7
Order By: Relevance
“…Findings of the current study were also in agreement with the study of Celik et al (2011) [23] and Nikki et al (2013), [24] who reported that pain score reduced during artery and vein needle puncture in the study group. On investigating correlations between the level of pain as measured by a numerical pain scale and the cushion cannulation technique, findings of the current study revealed that there was a negative correlation between stabilization of arm and level of pain.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Findings of the current study were also in agreement with the study of Celik et al (2011) [23] and Nikki et al (2013), [24] who reported that pain score reduced during artery and vein needle puncture in the study group. On investigating correlations between the level of pain as measured by a numerical pain scale and the cushion cannulation technique, findings of the current study revealed that there was a negative correlation between stabilization of arm and level of pain.…”
Section: Discussionsupporting
confidence: 82%
“…Also, it was reported to be 325. 22 and 94.46 pmp respectively for children aged [16][17][18][19][20][21][22][23][24][25] years. [2,3] An estimate that three to five adolescents pmp develop chronic renal failure annually, where 70% of them require dialysis for short periods and 23% require prolonged HD support.…”
Section: Introductionmentioning
confidence: 99%
“…It may be associated with depressive symptoms and lower quality of life in patients with HD [19]. Therefore, various methods have been attempted to reduce needle insertion pain [6][7][8][9][10][11]. The buttonhole technique has been expected to decrease pain more effectively than the rope-ladder or rotatingsite cannulation technique [6], but a recent metaanalysis concluded that no difference in cannulation pain was found between the 2 techniques in randomized controlled trials [7].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pain during needle insertion is the most common patient complaint regarding hemodialysis access [5]. Several approaches have been developed to minimize needle insertion pain, including buttonhole cannulation technique [6,7], lidocaine-containing local anesthetic cream/ patches [8,9], and lavender essential oil [10,11]. However, their effects are variable and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…On average, the hemodialysis patients undergo the procedure three times a week, each time lasting 3-4 hours. Moreover, the hemodialysis patients averagely experience the cannulation pain and skin puncture 10 times per month and this pain continues during the lifespan of the patient or until a successful kidney graft is performed (9)(10)(11). The frequent pain induced by fistula cannulation in hemodialysis may result in depression, decreased life quality, pain and agony, distress, and stress in these patients while pain management may lead to the acceptance of hemodialysis by these patients and their improved life quality (12).…”
Section: Introductionmentioning
confidence: 99%